Strategie przedsiębiorstw a środowisko naturalne - Leśniak-Łebkowska, Grażyna (Strategic Management and Natural Environment, 2008)
Contemporary strategic management is not sufficiently applied to identify and respond to environmental challenges of top importance for civilization development and its survival. Enhanced learning process is needed to change the awareness of managerial personnel, employees, customers and other stakeholders of sustainable development and their ability to create new interdisciplinary techniques at each level of strategic development to facilitate environmental innovations and entrepreneurial approach to shaping conditions for eco-entrepreneurship. This is a new area in strategic management, very attractive but to succeed it requires the integrated mechanisms of management and collaboration beyond traditional business perspective.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 195-207